Sistem Pakar Menggunakan Metode Forward Chaining dalam Identifikasi Kemampuan Siswa Terhadap Bidang Vokasi Pada Sekolah Menengah Kejuruan - Ilham Effendi; Gunadi Widi Nurcahyo (SEULANGA SYSTEM PUBLISHER, 2021)
The ability of students in the vocational field is a skill that students have in mastering certain applied skills. The ability of these students will be a benchmark in determining the choice to continue to higher education, work in the Industrial World Business World or do entrepreneurship. Constraints in assessing self-ability become a problem for students when completing school. The Expert System is an alternative to help students consult earlier to determine future directions. Developing the Expert System application provides an overview of students' abilities in the vocational field so that they are right on target in choosing a career. The data comes from interviews with class XII students of SMK Negeri 1 Kinali and data on the types of problems provided by experts. After data collection, analysis and problem solving were carried out using the Forward Chaining method by formulating rules or rules. The results of the rule formulation are implemented into a system that aims to determine the extent to which the PHP programming language is applied in identifying students' abilities in the vocational field in class XII of SMK Negeri 1 Kinali. Followed by testing the results so that the results of the process carried out with the help of the application are in accordance with the results of the process carried out manually. The result of the application is that it can provide early instructions for the right choice of determining students' abilities in the vocational field. The application of the Forward Chaining method that is applied to the system in determining students' abilities in the vocational field has an accuracy level of up to 80%, therefore the system can be said to be good enough to be applied.